2016
DOI: 10.9734/ejmp/2016/20760
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Indonesian Herbal Medicine, Phaleria macrocarpa (Scheff.) Boerl, for Targeting Multiple Malignancy Signaling Pathways: An Introductory Overview

Abstract: A wide variety of natural compounds have been recognized for targeting multiple malignancy signaling pathways and inducing apoptosis in various cancer cell lines from different origins. The chemical compositions of those substances present in plants contribute to their significant biological and medicinal value. In this review, we summarized our current findings and knowledge Mini-review Articleof bioactive compounds isolated from the Indonesian medicinal herb, Phaleria macrocarpa (Scheff.) Boerl, also known a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…Study on cervical cancer cell (CaSki) showed that gallic acid, a molecule isolated from P. macrocarpa, is able to inhibit cell proliferation of this cell [51]. In addition, gallic acid has also shown its anti-proliferation action on human cervical cancer HeLa and HTB-35 cells, but not on normal HUVEC cells [52]. This result supported the idea that gallic acid has selective dose-dependent cytotoxicity on cervical cancer cells only.…”
Section: Effect Of P Macrocarpa On Cervical Cancersupporting
confidence: 52%
See 1 more Smart Citation
“…Study on cervical cancer cell (CaSki) showed that gallic acid, a molecule isolated from P. macrocarpa, is able to inhibit cell proliferation of this cell [51]. In addition, gallic acid has also shown its anti-proliferation action on human cervical cancer HeLa and HTB-35 cells, but not on normal HUVEC cells [52]. This result supported the idea that gallic acid has selective dose-dependent cytotoxicity on cervical cancer cells only.…”
Section: Effect Of P Macrocarpa On Cervical Cancersupporting
confidence: 52%
“…It is the leading cause of cancer mortality in developing countries due to the high rate of HPV infection and lack of prevention steps in susceptible women. The most common HPV genotypes found in patients with invasive cervical cancer are 16,18,31,33,35,45,52 and 58. Out of these HPV genotypes, HPV 16 and 18 are classed as high-risk oncogenic types and are most likely to persist and progress from premalignant cervical disease to invasive cancer.…”
Section: Cervical Cancermentioning
confidence: 99%
“…Daily consumption of human beings contains a complex mixture of plant polyphenols which is flavonoids, as much as one gram of plant phenols per day is consumed in their diets [5]. A research group in China isolated and identified kaempferol-3-O-β-D-glucoside from Phaleria macrocarpa fruit [4].…”
Section: Phytochemical Testmentioning
confidence: 99%
“…Likewise, research had revealed that Phaleria macrocarpa fruit extracts can prevent arteriosclerosis and reduced cholesterol level in Japanese quails as well as primary culture of rat hepatocytes [5,6]. Phaleria macrocarpa has been used as a main ingredient in some healthy drink or tea, cosmetics and drugs [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation